PERGESERAN MAKNA PADA TRADISI REWANG DI DESA TAMBUSAI KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Ira Nurvika; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aimed to determine the shift in the meaning of Rewang tradition in Tambusai village Rumbio Jaya sub-regency Kampar regency. A few years ago tradition of Rewang in Tambusai village began to experience signs of shift. This research was qualitative method. This research used theory of social change and social action theory of Weber. This research used 7 people as informants consisted of 2 key informnts and 5 informants. With technique of sampling technique purposive sampling. The results of research obtained is a shift of tradition Rewang from the past with Rewang tradition in the present. Where in the past the meaning of the Rewang tradition is to ease the burden of the owner of the party, has a high economic value, and social capital to continue social relations. While the meaning of Rewang current tradition is to increase the burden of the owner of the intent, the materialist value on the Rewang tradition, the diminished intensity of community interaction, the meaning of Rewang for the social status of the owner, the economic meaning in Rewang tradition. As for the factors behind the shifting meaning of Rewang tradition that is the presence of cooking services and packaging change of Kenduri, interest in practicality, the attitude of the teenagers who are less enthusiastic about the Rewangan tradition,the reluctance of the owners to make trouble for the neighbors, and high confidence the chef. The most important factor behind the shift in Rewang tradition is the economic factor.Keywords: Meaning, Rewang Tradition, Javanese